The Effect of Dexmedetomidine on Emergence Agitation or Delirium in Children After Anesthesia—A Systematic Review and Meta-Analysis of Clinical Studies - Rao, Yuquan; Zeng, Ruifeng; Jiang, Xuebin; Li, Jun; Wang, Xiaocou (Frontiers in Pediatrics, 2020)
Background: We conducted this systematic review and meta-analysis to investigate the clinical effect of dexmedetomidine in preventing pediatric emergence agitation (EA) or delirium (ED) following anesthesia compared with placebo or other sedatives. Methods: The databases of Pubmed, Embase and Cochrane Library were searched till 8th January 2020. Inclusion criteria were participants with age<18 yr and studies of comparison between dexmedetomidine and placebo or other sedatives. Exclusion criteria included adult studies, duplicate publications, management with dexmedetomidine alone, review or meta-analysis, basic research, article published as abstract, letter, case report, editorial, note, method or protocol, and article presented in non-English language. Results: 58 Randomized Controlled Trials (RCTs) and 5 Case-control Trials (CCTs) including 7714 patients were included. The results showed that dexmedetomidine significantly decreased the incidence of post-anesthesia EA or ED compared with placebo [OR=0.22, 95% CI: (0.16, 0.32), I2=75, P < 0.00001], midazolam [OR=0.36, 95% CI: (0.21, 0.63), I2=57, P =0.0003], and opioids [OR=0.55, 95% CI: (0.33, 0.91), I2=0, P =0.02], whereas the significant difference was not exhibited compared with propofol (or pentobarbital) [OR=0.56, 95% CI: (0.15, 2.14), I2=58, P =0.39], ketamine [OR=0.43, 95% CI: (0.19, 1.00), I2=0, P =0.05], clonidine [OR=0.54, 95% CI: (0.20, 1.45), P =0.22], chloral hydrate [OR=0.98, 95% CI: (0.26, 3.78), P =0.98], melatonin [OR=1.0, 95% CI: (0.13, 7.72), P =1.00], and ketofol [OR=0.55, 95% CI: (0.16, 1.93), P =0.35]. Conclusion: Compared with placebo, midazolam and opioids, dexmedetomidine significantly decreased the incidence of post-anesthesia EA or ED in pediatric patients. However, dexmedetomidine did not exhibit this superiority compared with propofol and ketamine. With regard to clonidine, chloral hydrate, melatonin and ketofol, the results needed to be further testified due to only one included trial for each control drug.